Characterization of genomic alterations in primary central nervous system lymphomas - Zorofchian, Soheil; El-Achi, Hanadi; Yan, Yuanqing; Esquenazi, Yoshua; Ballester, Leomar Y. (Journal of neuro-oncology, 2018)
Purpose Primary central nervous system lymphoma (PCNSL) is a non-Hodgkin lymphoma that affects the central nervous system (CNS). Although previous studies have reported the most common mutated genes in PCNSL, including MYD88 and CD79b , our understanding of genetic characterizations in primary CNS lymphomas is limited. The aim of this study was to perform a retrospective analysis investigating the most frequent mutation types, and their frequency, in PCNSL. Methods Fifteen patients with a diagnosis of PCNSL from our institution were analyzed for mutations in 406 genes and rearrangements in 31 genes by next generation sequencing (NGS). Results Missense mutations were identified as the most common mutation type (32%) followed by frame shift mutations (23%). The highest mutation rate was reported in the MYD88 (33.3%), CDKN2A / B (33.3%), and TP53 (26.7%) genes. Intermediate tumor mutation burden (TMB) and high TMB was detected in 13.3% and 26.7% of PCNSL, respectively. The most frequent gene rearrangement involved the IGH-BCL6 genes (20%). Conclusions This study shows the most common genetic alterations in PCNSL as determined by a commercial next generation sequencing assay. MYD88 and CD79b are frequently mutated in PCNSL, IGH-BCL6 is the most frequent gene rearrangement and approximately 1/4 of cases show a high TMB. Mutations in multiple genes, in addition to high TMB and gene rearrangements, highlights the complex molecular heterogeneity of PCNSL. Knowledge about genetic alterations in PCNSL can inform the development of novel targets for diagnosis and treatment.